The autoinflammation-associated NLRC4V341A mutation increases microbiota-independent IL-18 production but does not recapitulate human autoinflammatory symptoms in mice - Eeckhout, Elien; Asaoka, Tomoko; Van Gorp, Hanne; Demon, Dieter; Girard-Guyonvarc’h, Charlotte; Andries, Vanessa; Vereecke, Lars; Gabay, Cem; Lamkanfi, Mohamed; van Loo, Geert; Wullaert, Andy (Frontiers in Immunology, 2023)
Background Autoinflammation with infantile enterocolitis (AIFEC) is an often fatal disease caused by gain-of-function mutations in the NLRC4 inflammasome. This inflammasomopathy is characterized by macrophage activation syndrome (MAS)-like episodes as well as neonatal-onset enterocolitis.Although elevated IL-18 levels were suggested to take part in driving AIFEC pathology, the triggers for IL-18 production and its ensuing pathogenic effects in these patients are incompletely understood.Methods Here, we developed and characterized a novel genetic mouse model expressing a murine version of the AIFEC-associated NLRC4 V341A mutation from its endogenous Nlrc4 genomic locus.Results NLRC4 V341A expression in mice recapitulated increased circulating IL-18 levels as observed in AIFEC patients. Housing NLRC4 V341A -expressing mice in germfree (GF) conditions showed that these systemic IL-18 levels were independent of the microbiota, and unmasked an additional IL-18inducing effect of NLRC4 V341A expression in the intestines. Remarkably, elevated IL-18 levels did not provoke detectable intestinal pathologies in NLRC4 V341A -expressing mice, even not upon genetically ablating IL-18 binding protein (IL-18BP), which is an endogenous IL-18 inhibitor that has been used therapeutically in AIFEC. In addition, NLRC4 V341A expression did not alter susceptibility to the NLRC4-activating gastrointestinal pathogens Salmonella Typhimurium and Citrobacter rodentium.As observed in AIFEC patients, mice expressing a murine NLRC4 V341A mutant show elevated systemic IL-18 levels, suggesting that the molecular mechanisms by which this NLRC4 V341A mutant induces excessive IL-18 production are conserved between humans and mice. However, while our GF and infection experiments argue against a role for commensal or pathogenic bacteria, identifying the triggers and mechanisms that synergize with IL-18 to drive NLRC4 V341A -associated pathologies will require further research in this NLRC4 V341A mouse model.